THE DNA BASE COMPOSITION OF INDIVIDUAL CHROMOSOMES AND CHROMOSOME SEGMENTS FROM CHIRONOMUS TENTANS - Daneholt, B. (The Rockefeller University Press, 1969)

(untitled)
The base composition of DNA was determined for individual chromosomes from the dipteran Chironomus tentans and for each one of six different segments of one of the chromosomes. The isolations were carried out by micromanipulation and the DNA purines were first extracted from the isolated components and afterwards separated by means of microelectrophoresis on a cellulose fiber. It was found that DNA from this material has an unusual composition corresponding to a guanine + cytosine content of about 30%. This composition was not a function of the polytenic condition but was also found for DNA from testis tissue. Furthermore Drosophila has a more traditional base composition for the bulk of DNA. Statistically significant variations in base data were found between whole chromosomes as well as between the segments from one of the chromosomes.